Domain Motion in 3-isopropylmalate dehydrogenase: A Strategy to Enhance its Thermal Stability - Zeily Nurachman; Tairo Oshima; Nobuo Tanaka (Institute for Research and Community Services (LPPM) ITB, 2003)
In order to elucidate the thermal properties of Thermus thermophilus 3-isopropylmalate dehydrogenase, mutant structures with mutations at the C-terminus were compared with each other. The structural movement can be anticipated from the structural changes among mutants in regions of a minor groove and pillar. Our previous studies revealed that the open-close movement of the active site groove antagonizes to that of the minor groove (like a paperclip) and the thermostability of the enzyme increases when the active site groove is closed. In the present study, it is shown that the motion of the enzyme mainly occurs in the first domain and strand D in the pillar structure is a hinge-bending region of the movement. The motion of the first domain to expand the minor groove may close the active site groove suggesting a mechanism for the enhanced thermal stability of 3-isopropylmalate dehydrogenase.